Evaluation of the Eighth Edition of the American Joint Committee on Cancer TNM Staging System for Gastric Cancer: An Analysis of 7371 Patients in the SEER Database - Long-Long Cao; Jun Lu; Ping Li; Jian-Wei Xie; Jia-Bin Wang; Jian-Xian Lin; Qi-Yue Chen; Mi Lin; Ru-Hong Tu; Chao-Hui Zheng; Chang-Ming Huang (Gastroenterology Research and Practice)
Objective. To investigate the validity of the 8th edition of the American Joint Committee on Cancer (AJCC) TNM staging system for gastric cancer. Methods. The clinicopathologic data of 7371 patients who were diagnosed with gastric cancer and had 16 or more involved lymph nodes (LNs) were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database and retrospectively reviewed. Results. Stage migration occurred primarily during stage III between the 7th and 8th edition TNM staging systems. Stages IIIB and IIIC in the 7th edition staging system were divided in the 8th edition and had obvious differences in survival rates (both P<0.001). The 8th edition TNM stages IIIC and IV showed similar survival rates (P=0.101). The prognosis of patients with T4aN3bM0 was not different from that of patients with TxNxM1 (P=0.433), while the prognosis of patients with T4bN3bM0 was significantly poorer than that of patients with TxNxM1 (P=0.008). A revised TNM system with both T4aN3bM0 and T4bN3bM0 incorporated into stage IV was proposed. Multivariable regression analysis showed that the revised TNM system, but not the 7th and 8th editions, was an independent factor for disease-specific survival (DSS) in the third step of the analysis. Further analyses revealed that the revised TNM system had superior discriminatory ability to the 8th edition staging system, which was also an improvement over the 7th edition staging system. Conclusion. The 8th edition of the AJCC TNM staging system is superior to the 7th edition for predicting the DSS rates of gastric cancer patients. However, for better prognostic stratification, it might be more suitable for T4aN3bM0/T4bN3bM0 to be incorporated into stage IV in the 8th edition TNM staging system.